The silver star : a novel - Walls, Jeannette (New York : Scribner, 2013)
Two motherless sisters--Bean and Liz--are shuttled to Virginia, where their Uncle Tinsley lives in the decaying mansion that's been in their family for generations. When school starts in the fall, Bean easily adjusts and makes friends, and Liz becomes increasingly withdrawn. Then something happens to Liz and Bean is left to challenge the injustice of the adult world
Keywords: Sisters -- Fiction; Self-actualization (Psychology) in adolescence -- Fiction